RESISTANCE, HUMANISM, AND ISLAMIC VALUE IN RATNA INDRASWARI IBRAHIM’S LEMAH TANJUNG - Masadi, Muhammad Anwar; Mansurudin, Susilo; Halimi, Halimi (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Islam as a discourse of resistance is not a contemporary issue. Islam occurred to encounter injustice and oppression. Ratna Indraswari Ibrahim, an author with disabilities, cannot be detached from the strength of her era. She wrote a novel Lemah Tanjung as a form of resistance to her era. As an author, she experienced essential events in her life. This research concerned on two things: the Islamic value in the resistance in Lemah Tanjung and the value of Islam's veiled resistance. This study implemented Faiclough's critical discourse theory which incorporated three basic components in analyzing text.The method administered was a qualitative. The data were collected from the novel Lemah Tanjung. The results of the study revealed that there was a hidden meaning in the content of Islamic resistance encompassing issues for the general public. The series of criticalities contains a hidden meaning that requires to be unveiled. That people desire enlightenment, liberation and previous issues which are necessary to be discussed openly. In this study, polite resistance possesses a significant contribution in society.